2022
DOI: 10.1103/physrevb.105.035115
|View full text |Cite
|
Sign up to set email alerts
|

Topological gaps in quasiperiodic spin chains: A numerical and K-theoretic analysis

Abstract: Topological phases supported by quasi-periodic spin-chain models and their bulk-boundary principles are investigated by numerical and K-theoretic methods. We show that, for both the un-correlated and correlated phases, the operator algebras that generate the Hamiltonians are non-commutative tori, hence the quasi-periodic chains display physics akin to the quantum Hall effect in two and higher dimensions. The robust topological edge modes are found to be strongly shaped by the interaction and, generically, they… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…Thus, in these special cases, the stably-homotopic classification of the self-binding states of N fermions is no more complicated than that of single fermion states. We point out that this has been already observed in numerical experiments (see [33]).…”
Section: Introduction and Main Statementssupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, in these special cases, the stably-homotopic classification of the self-binding states of N fermions is no more complicated than that of single fermion states. We point out that this has been already observed in numerical experiments (see [33]).…”
Section: Introduction and Main Statementssupporting
confidence: 79%
“…For example, for the many-body quantum system simulated in Fig. 11 of [33], the energy spectrum separates into several spectral islands and [33] found that the states associated with top spectral island display all the trades of selfbinding dynamics. On the other hand, the states associated with the other spectral islands display all the trades of a scattered dynamics (see Fig.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Further work can be found in [298,398,399,409,[414][415][416][417][418][419][420][421][422][423]. It should be also noted that noncommutative differential geometry developed in the late 70s and 80s by Connes [424] (building upon the earlier work of Grothendieck, Atiyah and Hirzebruch on topological Ktheory [425]), has been applied to the quantum Hall effect [426] and it offers an interesting avenue to study topological insulators in disordered and quasiperiodic systems [427][428][429]. From an engineering standpoint, group theoretic and topological concepts have been employed to geometrically design Reproduced from [401].…”
Section: Topologically Protected Statesmentioning
confidence: 98%